1987
DOI: 10.1002/j.1460-2075.1987.tb02364.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 69-kd and 100-kd forms of 2-5A synthetase in interferon-treated human cells by specific monoclonal antibodies.

Abstract: Communicated by A.M.MichelsonRecently, the existence of 40-kd and 46-kd 2-5A synthetases in interferon-treated cells has been confirmed by cloning and characterization of cDNA corresponding to these small size enzymes. By the use of specific monoclonal antibodies, we describe here two forms of high mol. wt 2-5A synthetases of 69 and 100 kd in human cells. The monoclonal antibodies immunoprecipitate either a 69-or a 100-kd 2-5A synthetase. These purified 2-5A synthetases in immune complex preparations are activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 37 publications
5
121
1
1
Order By: Relevance
“…IFN␣ treatment increases the RNase L level in mitochondria (Fig. 1) as it was shown for 2-5A synthetase (35). It was therefore conceivable that IFN␣ treatment could activate the 2-5A/RNase L pathway in mitochondria and promote the destabilization of mitochondrial mRNAs, as described here.…”
Section: -E) No Mitochondrial Mrnas Destabilization Is Observed Aftesupporting
confidence: 72%
See 1 more Smart Citation
“…IFN␣ treatment increases the RNase L level in mitochondria (Fig. 1) as it was shown for 2-5A synthetase (35). It was therefore conceivable that IFN␣ treatment could activate the 2-5A/RNase L pathway in mitochondria and promote the destabilization of mitochondrial mRNAs, as described here.…”
Section: -E) No Mitochondrial Mrnas Destabilization Is Observed Aftesupporting
confidence: 72%
“…These results presented the possibility that RNase L may degrade mitochondrial mRNAs after IFN␣ treatment. Furthermore, previous reports describe the presence of the p69 isoform of 2-5A synthetase in mitochondria (35,36). IFN␣ treatment increases the RNase L level in mitochondria (Fig.…”
Section: -E) No Mitochondrial Mrnas Destabilization Is Observed Aftementioning
confidence: 90%
“…Yanase and coworkers have shown that during IFNα induced apoptosis there is a release of cytochrome c from mitochondria, a decline in mitochondrial membrane potential and caspase 3 activation [121]. The different partners of the 2-5A pathway are localized in mitochondria: RNase L, RLI and p69 form of 2-5A-synthetase [100,122,123]. This pathway is induced by IFNα treatment and RNase L participates in mitochondrial mRNA degradation.…”
Section: ) Apoptosismentioning
confidence: 99%
“…The first molecular clone for an OAS was obtained by Michel Revel's lab [10]. Biochemical characterization of OAS proteins by Ara Hovanessian's lab [11][12][13][14] and Ganes Sen's lab [15][16][17][18][19] and a crystal structure by Rune Hartmann and Vivien Yee (in collaboration with Ganes Sen and Just Justesen) [20] have led to functional and structural insight into the OAS family of Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript.…”
Section: Background On the 2-5a/rnase L Systemmentioning
confidence: 99%